Counteracting disinformation among young people. Psychometric properties of the disinformation bystander intervention model scale, demographic differences, and associations with empathy - Sebastian Wachs; Maxime Kops; Estibaliz Mateos-Pérez; Manuel Gámez-Guadix (Computers in Human Behavior Reports)
This study investigated the psychometric properties of the newly developed Disinformation Bystander Intervention Model Scale (DISI-BIMS) among young people and explored its association with empathy and demographic differences. The sample consisted of 726 young people (Mage = 16.17, SD = 2.43) from Spain. Confirmatory factor analysis supported a model with five factors: Noticing disinformation, interpreting it as an Emergency, developing a sense of personal Responsibility, Knowing how to intervene, and Acting against disinformation. The findings indicated that the DISI-BIMS is a psychometrically sound measure that could aid in measuring the socio-cognitive processes of diverse young people when they decide to counteract disinformation. The results also showed that older participants reported higher means in Noticing and Knowing but lower in Emergency than younger participants. Girls reported lower means in Noticing and Knowing but higher means in Emergency than boys. Additionally, sexual minority participants and those with an immigrant background reported higher means in Emergency compared to heterosexual participants and those without an immigrant background, respectively. Finally, affective empathy was positively related to all five steps of the DISI-BIMS. Conversely, while beneficial for Emergency and Responsibility, cognitive empathy was negatively associated with Noticing and Knowing, indicating that it sometimes hinders immediate action due to over-rationalization and perspective-taking complexities. This distinction helps explain differential associations between empathy and the decision process upon counteracting disinformation. It highlights the importance of considering both facets of empathy in intervention efforts.